WHAT CAN HUMANITY DO TO HELP THE ANIMAL AND PLANT WORLD AND TO REDUCE THE DISAPPEARANCE OF RARE GIFTS OF NATURE? - Erkinova Fozila Dilshodovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. The rapid disappearance of rare animal and plant species poses a significant threat to biodiversity and ecosystem stability. This article explores various strategies that humanity can employ to protect and conserve these invaluable gifts of nature. Through a comprehensive literature analysis, methods employed in conservation efforts are evaluated, and their results are discussed. The study concludes with suggestions for future actions to ensure the long-term preservation of rare species and the ecosystems they inhabit.